The Quality of Educational Services Provided by the Arab Academy- Faculty of Finance and Banking from Graduate Students' Perspective, Sana'a - Abdulrahman Alsharjabi; Khadeeja Abdul-Hadi Daraan; Hussein Ali Alsarori (University of Science and Technology, Yemen, 2017)
The objective of this Study was to investigate the opinions of graduate students on the level of quality of educational services at the Faculty of Finance and Banking in Sana'a. The researchers used a questionnaire to collect the data. The questionnaire consisted of six sections: textbooks, instructional aids, library services, faculty, admission and registration procedures, and infrastructure. The main research question focused the level of the quality educational services provided at the faculty of Finance and Banking in Sana'a. The population of the study consisted of 379 students where 150 were randomly selected.  To answer the research question, the researchers used  the descriptive method. to The research results showed that the  students had a high satisfaction level of the services provided. In addition, the results showed that there were no differences among graduate students' opinions based on gender, age, program, area of specialization, and payment of tuition fees. Keywords: Service quality, Faculty of finance and banking, Graduate studies.